The Economic Impact of EU Sanctions on Trade between the EU and Russia - Bovt, Yuliia (2025)
This thesis examines the economic impact of European Union sanctions on bilateral trade between the EU and the Russian Federation from 2010 to 2024. Using Eurostat, UN Comtrade, and World Bank data, the study compares three periods—pre-sanctions (2010–2013), first-wave sanctions after the annexation of Crimea (2014–2021), and the comprehensive sanctions introduced following the 2022 full-scale invasion of Ukraine. The analysis shows a deep structural interdependence before 2014, followed by sharp declines in trade volumes, especially in energy, machinery, and agri-food sectors. EU restrictions on finance, technology, and energy reshaped Russia’s trade structure, accelerating import substitution and redirecting exports to partners such as China, India, and Turkey. The findings illustrate how sanctions altered long-standing trade patterns, weakened Russia–EU economic ties, and contributed to broader shifts in global trade alignment. The thesis highlights both the intended and unintended economic consequences of sanctions and provides insights into their long-term effectiveness as a tool of economic statecraft.